The Court Online Content Moderation: A Constitutional Framework - Rian Saputra; M Zaid M Zaid; Silaas Oghenemaro Emovwodo (Journal of Human Rights, Culture and Legal System, 2022)
This study aims to see and describe the practice of electronic justice in Indonesia based on the digital constitutionalism approach; as a concept that tends to be new, Digital Constitutionalism in its development also accommodates the due process online in scientific discourse. This research is normative legal research using a statutory and conceptual approach. Based on the research results, it is known that the practice of electronic justice in Indonesia still uses procedural law guidelines, which are conventional procedural law and internal judicial regulations. In contrast, the development of electronic justice that utilizes technological advances is insufficient to use conventional procedural law in its implementation because it is annulled. It has not been oriented to the protection of Human Rights as conceptualized in the Digital Constitutionalism discourse, which includes due process online. So the regulation of electronic justice in the future must be based on Digital Constitutionalism, which includes knowing the due process online by prioritizing the protection of human rights in a virtual scope from the provider of electronic judicial technology facilities.